Interrelationships of chemical properties, in vitro digestibility and ruminal degradability characteristics of protein sources - Bediye, S.; Ummuna, V.I.; Nsahlai, I.V.; Sileshi, Z.; Yami, A. (Ethiopian Society of Animal Production, 1996)
Associations among chemical properties, in vitro digestibility and ruminal degradability characteristics of herbaceous legumes, browse species and oilseed cakes were studied using correlation analysis based on a total of 50 feedstuff samples. Chemical properties were poorly related to in vitro organic matter digestibility (IVOMD). In browse species only crude protein (CP) was strongly associated with IVOMD while in oilseed cakes, CP and fiber components were strongly related to IVOMD. Fractional rates of ruminal degradability of N were strongly related to NDF content of herbaceous legumes, hemicellulose to cellulose ratio in browse species and lignin content in oilseed cakes. Potential degradability of N was poorly related to chemical properties of herbaceous legumes and browse species but strongly related to CP and fiber components in oilseed cakes. Potential degradability of OM was poorly related to IVOMD of herbaceous legumes and browse species but strongly related in oilseed cakes. Fractional rate of organic matter disappearances accounted for more than 85 percent of the variation in IVOMD of browse but only up to 10 percent in herbaceous legumes and oilseed cakes. Hourly OM disappearances and IVOMD were poorly related to IVOMD in hrbaceous legumes but strongly related in the ranges of 24-48 hr in browse and 36-48 h in oilseed cakes. Chemical properties of protein sources were poorly related to biodegradability suggesting need for basic research to determine the fundamental properties of cell walls that constrain their intrinsic digestion rates and potential degradability.